Social Disparities in Education in Sub-Saharan African Countries : Gender, geographical location and family income - (:unkn) unknown (My University, 2006)
In this paper we have two complementary objectives: the first consists in proposing a description of the magnitude of social disparities that exist in the systems of education of Sub-Saharan African countries; we focus on recent data but we put also these data in a time perspective. The second objective aims at identifying some of the factors that may explain these disparities or the impact of the actions targeted to their reduction.
Keywords: African Research